2020
DOI: 10.1007/s00330-020-07287-6
|View full text |Cite
|
Sign up to set email alerts
|

MR 4D flow-based mean pulmonary arterial pressure tracking in pulmonary hypertension

Abstract: Objectives Longitudinal hemodynamic follow-up is important in the management of pulmonary hypertension (PH). This study aimed to evaluate the potential of MR 4-dimensional (4D) flow imaging to predict changes in the mean pulmonary arterial pressure (mPAP) during serial investigations. Methods Forty-four adult patients with PH or at risk of developing PH repeatedly underwent routine right heart catheterization (RHC) and near-term MR 4D flow imaging of the main pulmonary artery. The duration of vortical blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 46 publications
1
17
0
Order By: Relevance
“…Reiter et al also reported that MR-driven mPAP, as calculated by the change in the duration of vortical flow, was correlated with the change in RHCdriven mPAP. 49 A secondary morphological change in PH, the dilation of the pulmonary arterial trunk, may have influenced the formation of vortex flow. However, in a study of normal subjects, vortical flow formation was reported to occur in approximately 3% of subjects without a history of PH.…”
Section: D Flow For Pulmonary Hypertensionmentioning
confidence: 99%
“…Reiter et al also reported that MR-driven mPAP, as calculated by the change in the duration of vortical flow, was correlated with the change in RHCdriven mPAP. 49 A secondary morphological change in PH, the dilation of the pulmonary arterial trunk, may have influenced the formation of vortex flow. However, in a study of normal subjects, vortical flow formation was reported to occur in approximately 3% of subjects without a history of PH.…”
Section: D Flow For Pulmonary Hypertensionmentioning
confidence: 99%
“…4D flow CMR, an emerging time-resolved phasecontrast technique with flow velocities encoded simultaneously in three directions allows comprehensive measurement of blood flow dynamics in the heart and large vessels with full volumetric coverage throughout the cardiac cycle [4][5][6]. It has been applied to investigate pulmonary artery hemodynamics in patients with PAH [7][8][9][10][11][12] but studies on intracardiac blood flow are scarce. Employing 4D flow CMR, Han et al [13] demonstrated altered RV kinetic energy (KE) parameters derived from computational analysis of individual pathlines and velocities within the RV between PAH patients and controls.…”
Section: Introductionmentioning
confidence: 99%
“…The vortex duration method was first introduced by Reiter et al who went from using a single slice with 3D velocity encoding initially [ 16 ], in order to harvest signal-to-noise-ratio by using the in-flow effect. A 4D-flow approach was used more recently by this author [ 17 , 18 ] and several other groups [ 10 , 15 ], but this technique is not currently used in clinical practice. This present work is therefore important to further validate and promote such an approach.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have already assessed the ability of cardiac MRI to detect PH and to quantify it, based on the right ventricular function and mass, the curvature of the interventricular septum [ 7 ], the flow rate across the pulmonary artery [ 8 ], the wall shear stress [ 9 , 10 ] and the presence of vortices in the pulmonary artery using 4D flow MRI [ 11 , 12 , 13 ]. In addition, it has been reported that the duration of the vortices in the pulmonary artery was related to the mPAP and could be used to detect and quantify PH [ 14 , 15 , 16 , 17 , 18 ], in patients with different causes of PH.…”
Section: Introductionmentioning
confidence: 99%